Problems of trade policy - Meier, Gerald M. (New York : Oxford University Press, 1973)
This book deal with policy problems in international political economy and problems of world monetary order and also problem of cooperation for development.
Companion volume to the author's Problems of cooperation for development.
Includes bibliographical references.
oo 02/11/2018
Loans
Keywords: Commercial policy; International economic relations